PENGARUH KUALITAS AUDITOR TERHADAP MANAJEMEN LABA (Studi Empiris pada Perusahaan Non Keuangan yang Terdaftar di BEI Tahun 2009-2011) - Yulia Rachmawati; Fuad Fuad (Diponegoro Journal of Accounting, 2013)
This study aims to analyze the association between the magnitude of earnings management and auditor quality. The information asymmetry motivates management to execute manipulate performance with earnings management. Auditor quality use industry specialist auditor and big four auditor. The Modified Jones Model is used to measure discretionary accruals (the proxy for earnings management). The sample used in this research was the secondary data from annual report of non financial companies which listed on Bursa Efek Indonesia in 2009-2011. The sample was taken using the method of purposive sampling, and those meeting the selection criteria were also taken. The sample used counts of 756 companies. The statistic method used was multiplied analysis linear regression with hypothesis testing of statistic t and F test. The results provide evidence that industry specialist auditor significantly influence the earnings management. Nonetheless, big four auditor wasn’t significant influence to the earnings management.